Perbedaan khasiat antibakteri bahan irigasi antara hidrogen peroksida 3% dan infusum daun Sirih 20% terhadap bakteri mix - Dian Agustin W (Dental Journal (Majalah Kedokteran Gigi), 2005)
Piper betle folium was Indonesian’s traditional medicinal herb. The most important element in its was phenol with has antibacterial effect. H2O2 3% was commonly used because readily available, can lift up debris from root canal preparation. The purpose of this study was to determine the antibacterial effect of two solutions: hydrogen peroxide 3% and piper betle folium infusum 20% to bacterial mix invitro. The twenty specimens are divided into two groups. The result is statistically analyzed using Wilcoxon man whitney test. This study showed that piper betle folium infusum 20% had greater antibacterial effect than H2O2 3% solution.